Intermediate Accounting (Book). - Bruns, William J.; Langenderfer, Harold Q. (The Accounting Review, 1969)
Reviews the book, "Intermediate Accounting," by Glenn A. Welsch, Charles T. Zlatkovich and John Arch White.